Son of the mob - Korman, Gordon (Hyperion Books for Children, 2002)
Seventeen-year-old Vince's life is constantly complicated by the fact that he is the son of a powerful Mafia boss, a relationship that threatens to destroy his romance with the daughter of an FBI agent.